2022
DOI: 10.3390/agronomy12061286
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Iron Inhibited Maize Straw Decomposition by Suppressing Microbial Communities and Enzyme Activities

Abstract: In order to study the linkages between the crop straw decomposition rate and the change in soil biological properties after the straw returned to the soil with different iron (Fe2+) contents, a 180-day incubation experiment was performed to examine the decomposition of maize straw (MS) under three Fe2+ levels, i.e., 0, 0.3, and 1 mg g−1. Enzyme activities regarding straw decomposition and microbial communities under 0 and 1 mg g−1 Fe addition were also detected. The results showed that Fe2+ addition significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…of oil absorption using the one-factor-at-a-time (OFAT) and response surface methodology (RSM) approaches. The study found that under the conditions of 128 °C temperature and 36 (v/v)% oil concentration, CG demonstrated an efficiency of 93.54% in absorbing 22.45 mL of oil, while keeping the packing density and time constant at 30 min and 0.20 g/cm 3 , respectively. Compared to other natural sorbents, CG's oil/water selectivity properties make it a cost-effective method with high potential for combating oil spills.…”
Section: Application Of Cogon Grass (Imperata Cylindrica) As Biosorbe...mentioning
confidence: 95%
See 3 more Smart Citations
“…of oil absorption using the one-factor-at-a-time (OFAT) and response surface methodology (RSM) approaches. The study found that under the conditions of 128 °C temperature and 36 (v/v)% oil concentration, CG demonstrated an efficiency of 93.54% in absorbing 22.45 mL of oil, while keeping the packing density and time constant at 30 min and 0.20 g/cm 3 , respectively. Compared to other natural sorbents, CG's oil/water selectivity properties make it a cost-effective method with high potential for combating oil spills.…”
Section: Application Of Cogon Grass (Imperata Cylindrica) As Biosorbe...mentioning
confidence: 95%
“…[2]. (B) Redundancy analysis depicting the relationship between the bacterial phyla and enzyme activities [3]. (C) Structural equation modeling (SEM) of the effects of submergence on organic carbon pool as a result of submergence-induced changes in soil acidification and soil environment [4].…”
Section: Does Straw Returning Amended With Straw Decomposing Microorg...mentioning
confidence: 99%
See 2 more Smart Citations
“…Frontiers in Bioengineering and Biotechnology frontiersin.org 4 Application of microorganisms based fermentation to pretreat crop straw 4.1 Decomposition process of crop straw Zhang et al (2014) analyzed 784 crop straw samples, including cotton stalk samples, wheat straw, rape stalk, rice straw, and corn stover, collected from different regions of China, discovering that crop straw contains some essential elements, including carbon, nitrogen, sulfur, phosphorus, and potassium (Zhang et al, 2014;Wang et al, 2020). It was observed that in nature, crop straw can be decomposed gradually by bacteria, fungi, and other microbes with the assistance of hemicellulase, cellulase and ligninase (Henriksen and Breland, 2002;Jin et al, 2022). For example, Ji et al (2018) reported that Methanosarcina and Methanothrix as well as hydrogentrophic Methanocella could be regarded as the important archaeal taxa involved in rice straw degradation (Ji et al, 2018).…”
Section: Kumar Et Al (2013)mentioning
confidence: 99%